2020
DOI: 10.3390/nu12041056
|View full text |Cite
|
Sign up to set email alerts
|

Salt Taste Genotype, Dietary Habits and Biomarkers of Health: No Associations in an Elderly Cohort

Abstract: A small amount of emerging research has observed variations between individual sensitivity, preference and intake of salt in the presence of single nucleotide polymorphisms (SNP) on the genes encoding salt taste receptors. Sodium intake is a significant risk factor for common diseases in elderly populations such as hypertension and cardiovascular disease; however, this does not fully explain the risk. Research into the influence of salt taste genetics on diet quality is yet to be undertaken and current researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The association between salt intake and blood pressure is addressed in this Special Issue. Ferraris et al [6] found (see above) that SNP for the gene encoding the salt receptor, TRPV1, was not associated with a variation in salt intake in an elderly cohort. Consistently, neither systolic nor diastolic blood pressure varied by genotype.…”
Section: Blood Pressure Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between salt intake and blood pressure is addressed in this Special Issue. Ferraris et al [6] found (see above) that SNP for the gene encoding the salt receptor, TRPV1, was not associated with a variation in salt intake in an elderly cohort. Consistently, neither systolic nor diastolic blood pressure varied by genotype.…”
Section: Blood Pressure Regulationmentioning
confidence: 99%
“…Thus, oral microbiota may influence food preference. The possible association between salt taste genotype and eating behavior has been studied by Ferraris et al [6] in a large-sized (n = 536) and well-characterized elderly cohort in Australia. They evaluated the association between the occurrence of single nucleotide polymorphisms (SNPs) for the TRPV1-encoding gene and individual salt intake.…”
Section: Eating Behaviormentioning
confidence: 99%
“…DNA samples were stored at 20 °C prior to genotyping. Genotyping was carried out via qPCR (QuantStudio 7 Flex Real-Time PCR) with TaqMan™ SNP Genotyping Assays (Applied Biosystems™, ThermoFisher Scientific, CA, USA) and TaqMan™ Genotyping Master Mix according to the TaqMan™ user guide [ 56 , 57 ]. Participants were included in this study only upon successful genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic data (age, sex, income, education, history of smoking) were collated through interviewer-administered questionnaires (30,32,33). Body dimension (hip circumference, waist circumference, and height) and weight measurements were collected adhering to the standards of the International Society for the Advancement of Kinanthropometry (ISAK) (34).…”
Section: Demographics and Anthropometricsmentioning
confidence: 99%
“…Blood pressure (BP) measurements were taken from both arms by qualified clinical staff using an OMRON IA2 machine (32). Physical limitation preventing measurement, repetitive differences in systolic BP of >10 mmHg and diastolic BP of >6 mmHg, very high BP curtailing measurement and machine error were exclusion criteria (32). Following the World Health Organisation's guidelines, hypertensive was defined as recording systolic BP of ≥140 mmHg and diastolic BP of ≥90 mmHg (41).…”
Section: Blood Pressure Readingsmentioning
confidence: 99%